Reaping the benefits from investments in breeding in Mozambique - International Potato Center (2014)
This five year project (2009-2014) financed by the Mozambique USAID mission, together with support from the Office of Disaster Assistance for 2 years, supplied at least 200,000 households in 7 provinces of Mozambique with improved, pro-vitamin A rich sweetpotato varieties.